FAKTOR-FAKTOR YANG MEMPENGARUHI LITERASI KESEHATAN MASYARAKAT DI PUSKESMAS BANGUNTAPAN I BANTUL D.I.Y - Wahyuningsih, Tutik (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2019)
Background: The results of the preliminary study conducted can be seen that the level of public health literacy at puskesmas banguntapan I still relatively low this is known when researchers conducted a trial of 10 respondents by using NVS (New Vital Sign) of the 6 questions about an ice cream nutrition label 7 of the 10 respondents had a low literacy level with a score of 1-2 classified as a low category, researchers used the ice cream nutrition label because to determine the lavel of public health literacy the treatment at puskesmas banguntapan I. Objective: to find out the factor age, education, work that influence health at literacy at Puskesmas Banguntapan I. Methods: This type of research uses quantitative descriptive with cross sectional design. The instrument of this study used the NVS questionnaire (Newest Vital Sign). The variables measured are age, education, work that is associated with health literacy. Primary data were analyzed using the chi square test. The sample in this study amounted to 100 respondents in the Puskesmas Banguntapan I. Result : there is influence of age on health literacy (p=0,038%<0,05). There is an influence of education on health literacy (p=0,000<0,05), there is effect of work on the level of health literacy (p=0,043<0,05). Conclusion: Based on the results of data analysis there is an influence between age, education, and work on health literacy.